British council kids technological tool in the development of listening skill in seventh grade students - Guamba Almagro, Dorian Sebastian (2023)
This research explores the use of British Council Kids technology tools in the development of listening skills in seventh graders. The study is based on the need to explore the use of tools that arise from children's development with technology and their contact with it in the development of English as a foreign language. The project used a qualitative method of phenomenological and exploratory character, since it intends to analyze a little explored area of knowledge and also tries to conceive a general knowledge of the impact of the technological tool British Council Kids in the development of the ability to listen. It was carried out in the School of Basic Education "Lic. Jaime Andrade Fabara" with 89 students of the seventh year of basic education who were exposed to the technological tool British Council Kids during the whole school year 2022-2023 once a week together with the English teacher in order to collect their experience through interviews and observations of the teacher. The data collected were analyzed by means of the Thematic Analysis method which allowed to divide opinions into advantages and disadvantages that have been found as well as their impact on the development of the students. The results showed that the use of technological tools had a positive impact on students' listening skills, as well as on their motivation and engagement in the learning process. The report concludes with recommendations for future research and implications for language teaching and learning.